Derivatif Keuangan dan Penghindaran Pajak pada Perusahaan Manufaktur di Indonesia - Fransisca Agustin (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2021)
Understanding the impact of financial derivatives on tax avoidance is the purpose of this article. Capital intensity, return on assets, and leverage are control variables. Manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2012 to 2016 became the population in this research. After sampling with purposive sampling technique, the amount of data obtained is 51 data. Then, descriptive analysis techniques and multiple linear regression were carried out to prove the built hypothesis, so that it was concluded that financial derivatives have a negative effect on tax avoidance.